Modelling choice of fuelwood source among rural households in Malawi: A multinominal probit anlaysis - Jumbe, C.B.L.; Angelsen, A. (2011)
This paper addresses two questions: what determines household's choice of fuelwood source and, what are the environmental consequences of fuelwood collection choices? We address these questions by estimating the multinomial probit model using survey data for households surrounding Chimaliro and Liwonde forest reserves in Malawi. After controlling for heterogeneity among households, we find strong substitution opportunities across fuelwood collection sources. Attributes of the fuelwood sources (size and species composition) and distance to the sources are the most important determinants of fuelwood choice. Further results show that customary managed forests generate environmental benefits by reducing pressure on both plantation forests and forest reserves. These findings support the need to strengthen community-based institutions to manage local forest resources.